DEVELOPMENT OF AN ARTIFICIAL INTELLIGENCE BASED SYSTEM FOR NUTRIENT DELIVERY TO GREENHOUSE GROWN CROPS (2023)
Applying nutrients to crops either on the field or in a greenhouse has been a manual process, especially in developing countries where farmers or greenhouse attendants introduce nutrients based on intuition, or at specific intervals, not knowing exactly when a crop requires the said nutrients. This is one of many reasons why artificial intelligence has been introduced into the agricultural sector. This project was designed to develop an artificial intelligence-based system for the automatic delivery of nutrients to greenhouse-grown crops. The system was built with an Arduino microcontroller serving as the brain box of the system, a soil Nitrogen, Phosphorus and Potassium (NPK) sensor for reading nutrients level, an organic light-emitting diode which display. +he specific nutrient level in mg/kg, while a solenoid valve was incorporated into the delivery mechanism. T. e da*r was logged onto a secure digital (SD) card via SD module installed on the Arduino board. The microcontroller was configured to interpret the varied states of the soil as relayed by the soil sensor; and this involved data capture from NPK sensor, data processing to determine when to release nutrients, and delivery of nutrients if the solenoid valve is activated. The system was evaluated on soil whose nutrients were leached out, placed in a greenhouse, and the performance was satisfactory